Sufisme dalam Pandangan Muslim Modernis Awal: Telaah Pemikiran Tasawuf Kiai Moechtar Boechari (1899-1926) - Ali, Mohamad (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2019)
This research tries to find sufism thought by early modernist muslim from Surakarta, Kiai Moechtar Boechari (1899-1926), by tracing his religious view and Sufism thought. He was a santri and friend of K.H. Ahmad Dahlan (1868-1923) who pioneered in establish Muhammadiyah branch Surakarta. In general, as modernist muslim movement, MuhamÂmadiyah is considered as anti-sufism. In contrast to that, Kiai Boechari paid attention to Sufism by writing a thin book, Tasawoef Tjekakan. This intellectual position is somewhat different from the mainstream modernist Islam movement. To explore this issue, this paper uses historical method by Berkhoferâ€Ÿs situational approach. The result of the research points out, that firstly, religious view of Kiai Boechari is a modernist with authentic formulation, that is: purifying Tauhid, awakening scientific ethos, promoting movement of Islamic modernist, preaching Islam softly, and appreciating womenâ€Ÿs equality. Secondly, the character of Kiai Boechariâ€Ÿs thought on Sufism seems to resemble Imam Al-Ghazaliâ€Ÿs mysticism of personality (transcendental mysticism), only that he modified by reducing zuhud station in order for a sufi to be involved dynamically in many aspects of life.Keywords: Kiai Moechtar Boechari, modernist muslim, sufism, SurakartaÂ Penelitian ini berupaya mengungkap pemikiran tasawuf seorang muslim modernis awal asal Surakarta, Kiai Moechtar Boechari (1899-1926), dengan cara melacak pandangan keagamaan dan corak pemikiran tasawufnya. Dia merupakan santri dan sahabat K.H. Ahmad Dahlan (1868-1923) yang turut mendirikan Muhammadiyah cabang Surakarta. Pada umumnya, sebagai gerakan Islam modernis, Muhammadiyah dipandang anti-tasawuf. Berbeda dengan itu, Kiai Boechari memberi perhatian pada sufisme dengan menulis buku tipis, Tasawoef Tjekakan. Posisi intelektual yang demikian seolah-olah menempatkannya berada â€œdi luar arus utamaâ€ gerakan Islam modernis. Untuk mengeksplorasi masalah tersebut, peneliti memakai metode sejarah dengan pendekatan situasional Berkhofer. Hasil penelitian menunjukkan pertama, pandangan keagamaan Kiai Boechari berhaluan modernis dengan formulasi yang otentik, yakni: memurnikan tauhid; membangkitkan etos keilmuan, aktif di gerakan Islam modern, mendakwahkan Islam dengan kelembutan, dan menghargai kesetaraan perempuan. Kedua, pemikiran tasawuf Kiai Boechari bercorak mistik kepribadian (transendental mistik) seperti halnya Imam Al-Ghazali. Lebih dari itu, dia memodifikasinya dengan tidak memasukkan tangga zuhud, agar sufi lebih dinamis menapaki berbagai aspek kehidupan.Kata kunci: Kiai Moechtar Boechari, muslim modernist, sufisme, Surakarta